Benería, Lourdes; Berik, Günseli i Floro, Maria S. (2016). Gender, development and globalization: Economics as if all people mattered (second edition) - Casellas, Antònia (Documents d’Anàlisi Geogràfica, 2019)
Benería, Lourdes; Berik, Günseli i Floro, Maria S. (2016) Gender, development and globalization: Economics as if all people mattered (second edition) Nova York: Routledge, 320 p. ISBN 978-0415537490